Polymer nanocomposites. Part II. Nanocomposites based on thermoplastic polymers and layered silicates - Kacperski, M. (Polimery, 2022)
A review (years 2000-2001) concerns the methods of synthesis and properties of nanocomposites containing layered silicates and thermoplastic polymers such as polyamides, polyolefines (polypropylene, polyethylene), polystyrene and styrene copolymers, poly(ethylene terephthalate) and poly(methyl methacrylate). The methods of composites preparing either by mixing of the components in melt or by swelling of montmorillonite (MMT) in the monomers (substrates in case of PET) as well as the ways of MMT modification have been discussed. Special attention has been paid to the advantageous properties of nanocomposites such as flexural strength, stress at break, flexural modulus, impact strength and thermal resistance.